Cooperative breakups induced by drop-to-drop interactions in one-dimensional flows of drops against micro-obstacles1. Issue 12 (28th March 2015) - Schmit, Alexandre; Salkin, Louis; Courbin, Laurent; Panizza, Pascal
<x xml:space="preserve">Abstract</x> We present a model describing the complex breakup dynamics of one-dimensional trains of drops against rectangular micro-obstacles.